Channel modeling and measurements in waveguide-like structures - Mao, Xiaohong (2012)
In this thesis, a detail study on channel characterization and modeling of the propagation within waveguide-like structures, namely; the lift shaft and the cargo hull of a merchant ship is performed. These channels are studied for military applications such as urban warfare and battlefield communication network onboard ships. For urban areas, although the environment can be different from one to the next, high-rise buildings with lift shafts can be commonly found. Due to the boxed shaped hollow structure of the lift shaft, guiding effect associated with the lift shaft channel can be a reliable link. The propagation mechanisms along a lift shaft in an urban area are examined based on experimental study and verified by ray-tracing simulation results. The signal variations caused by the opening/closing of the lift door and movement of the lift car are modeled in detail. On board the ship, the aim is to establish communication between two key locations, the bridge room on the top and the engine control room at the bottom. These are crucial locations in terms of trying to take control over the ship. Therefore, the knowledge of wave propagation mechanisms between these locations within the ship is required. In this study, a series of experimental work has been conducted along the lift shaft onboard a merchant ship. Waveguide-like effect and signal variations associated with the lift shaft channel is examined and compared with the results obtained from urban area. Moreover, the waveguide-like effect along the cargo hull of the merchant ship is studied based on experimental and simulation results. Small-scale channel characteristics are analyzed based on the guiding effect. Finally, besides the direct propagation in VHF band, a relay system is proposed to enable the wideband propagation between the two key locations in the military UHF band and popular ISM band. As the analogues waveguide effect of the cargo hull can ensure the communication quality, the relay system is suggested to be deployed inside the cargo hull.